Impact of halalan toyyiban principles on consumer trust in sustainable food security in Malaysia: a conceptual study - Abdul Razak, Dzuljastri; Che Embi, Nor Azizan; Muhammad Arijie, Ulfy (IIUM Press, 2026)
This conceptual article establishes a theoretical background that illustrates the relationships between the implementation of halalan toyyiban principles and their role in shaping consumer trust and enhancing sustainable food security in Malaysia. This study develops a conceptual framework based on Islamic ethical philosophy, trust theory, and sustainability discourse. It contends that halalan toyyiban is both a religiously mandated concept and a holistic quality and sustainability framework that influences customer perceptions and systemic resilience. The suggested conceptual model links three dimensions, halalan toyyiban compliance and certification, food safety and cleanliness, and ethical farming and production practices to consumer trust, which mediates their total influence on the sustainability of national food security. Consumer trust is argued to be a spiritual and moral link between personal faith-based certainty and larger sustainable benefits. This study seeks to develop a trust-based sustainability context for halal food systems, expand halal research to include ethical considerations alongside legal ones, and inform policy discourse on the governance of Malaysia's food security